IMPLEMENTASI PROGRAM “CHRISTCHURCH CALL” PASCA SERANGAN TERORISME DI CHRISTCHURCH TAHUN 2019 - Luthfi A.S, Ahmad; Saeri, Mhd. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
After the terrorist attack in Christchurch, New Zealand on March 15, 2019, Prime Minister Jacinda Ardern initiated a political meeting held in Paris on May 15, 2019, to establish international cooperation in countering terrorism known as the Christchurch Call, along with French President Emmanuel Macron. This research employs a qualitative descriptive method, where data collection is conducted through literature review and analysis of various sources such as books, journals, official websites, and reports related to the implementation of the Christchurch Call program following the terrorist attack in Christchurch in 2019. The theoretical framework used in this research is Counter Terrorism, where actors involved engage in counteraction against acts of terrorism occurring in New Zealand. The research findings indicate that efforts to halt terrorism involve the implementation of the Christchurch Call program, where New Zealand collaborates with France to execute the program, supported by various entities including several countries, international organizations, and technology and communication companies. The results of the program, up to this point, have received positive responses from various parties, despite some shortcomings. It is hoped that the program will continue to evolve to operate optimally in the future. Key Word : Christchurch Cal, Terrorism, Extrimist